Dark chocolate for children's blood pressure: randomised trial. Issue 7 (9th June 2012) - Chan, Eunice K; Quach, Jon; Mensah, Fiona K; Sung, Valerie; Cheung, Michael; Wake, Melissa
Abstract : Background: Higher adult blood pressure, even without hypertension, predicts cardiovascular outcomes, and is predicted by childhood blood pressure. Regular dark chocolate intake lowers blood pressure in adults, but effects in children are unknown. Aim: To examine the feasibility of school-based provision of dark chocolate and its short-term efficacy in reducing mean group blood pressure. Methods: 194 children (aged 10–12 years) were randomised by class to intervention (7 g dark chocolate daily for 7 weeks, n=124) or control (n=70) groups; 98% and 93% provided baseline and follow-up measurements, respectively. Results: Intervention and control students had similar systolic (mean difference 1.7 mm Hg, 95% CI −0.6 to 4.1) and diastolic (−1.2 mm Hg, 95% CI −3.6 to 1.3) blood pressure, anthropometry and well-being at outcome. Conclusion: Results show that providing dark chocolate is feasible and acceptable in the school setting. For a definitive trial, the authors recommend a larger sample, endovascular function measures, and consideration of higher antioxidant 'dose' by virtue of duration and/or content.